Respostas

  • Usuário do Brainly
2013-02-21T23:13:12-03:00

Temos que:

 

\text{log}_2(\text{x}+3)-\text{log}_2(\text{x}-1)=2

 

Como as bases são iguais, podemos afirmar que:

 

\dfrac{(\text{x}+3)}{(\text{x}-1)}=2^2

 

Donde, obtemos:

 

\dfrac{(\text{x}+3)}{(\text{x}-1)}=4

 

Como \text{mmc}(\text{x}-1, 1)=\text{x}-1, segue que:

 

\text{x}+3=4\cdot(\text{x}-1)

 

\text{x}+3=4\text{x}-4

 

4\text{x}-\text{x}=3+4

 

3\text{x}=7

 

Logo, chegamos à conclusão de que:

 

\text{x}=\dfrac{7}{3}

1 5 1